Mothers Toddler Knowledge About Giving And Method Of Making 4 (Four) Star Complementary Feeding In Stunting Prevention Efforts - Neti Sulami; Yati Purnama; Dian Mariza (Sean Institute, 2023)
Complementary food must meet the nutritional needs of 4 stars which must contain micro and macronutrients consisting of carbohydrates, protein, fat, vitamins and minerals. If complementary foods are not introduced around the age of 6 months, or if they are given inappropriately, they can be a risk factor for stunting. In giving MPASI, the things that need to be considered are the sufficient amount, time, texture, variety, method of administration, and principles of cleanliness. This research is a quantitative descriptive study to find out the knowledge of mothers of toddlers aged 6-12 about giving and how to make MPASI by calculating the frequency distribution. The results showed that the knowledge of mothers of toddlers aged 6-12 months about the purpose and benefits of giving a healthy menu of MPASI 4 stars was in the less category, namely 92% and 72%, the knowledge of mothers of toddlers aged 6-12 months about the nutritional needs of MPASI in the less category was equal to 92%, knowledge of mothers of toddlers aged 6 – 12 months about the Impact of Providing MPASI Healthy Menu is in the less category, namely 84%, types of MPASI given to toddlers aged 6 – 112 months are mostly processed factories, namely 90%, and accuracy of mothers of toddlers age 6 – 12 months about the accuracy of the method of cooking/texture in the inappropriate category, which is 71%.